Three Plays of Cha Fra Dcosta - Cha Fra Dcosta; REGO (Sylvia) Tr (Mangaluru St Aloysius Prakashana, 2024)
Dr Sylvia Rego, Department of English, St Aloysius (Deemed to be University)
Keywords: Teacher Unmarried (Aunkwar Mesthri); The Man with a Heart of Gold (Bangar Monis); Jillas Men (Jillache Novre)